Associations of serum alkaline phosphatase level with all-cause and cardiovascular mortality in the general population - Yan, Wei; Yan, Ming; Wang, Hui; Xu, Zilong (Frontiers in Endocrinology, 2023)
Background and Aims: There are few population studies on the associations of serum alkaline phosphatase (AlkP) with all-cause and cardiovascular mortality. We aimed to investigate the relevancy of serum AlkP with all-cause and cardiovascular mortality in the general population.Results: Our research included 34,147 adults in the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2014. Cox proportional hazards regression models were used to assess the associations of serum AlkP with all-cause and cardiovascular mortality. Mediation analysis was used to analyze mechanisms that might link serum AlkP to all-cause and cardiovascular mortality. After 139.7 ± 57.8 months of follow-up, 5413 participants experienced all-cause death and 1820 participants experienced cardiovascular death. Mortality rates per 1000 person-years from various diseases increased with increasing serum concentrations of AlkP, especially all-cause death, cerebrovascular disease and cardiovascular death. High serum AlkP levelsignificantly increased all-cause and cardiovascular mortality. After multivariate adjustment, the highest AlkP group had the highest risk to experience all-cause (hazard ratio [HR] = 1.30, P < 0.001) and cardiovascular mortality (HR = 1.39, P < 0.001) than the lowest AlkP group. γ-glutamyl transpeptidase (GGT) (13.33% and 15.79%), followed by Vitamin D (8.33% and 7.14%) and C-reactive protein (CRP) (7.69% and 10.35%) were identified as possible major mediators.Conclusions: Higher AlkP concentrations were associated with higher all-cause and cardiovascular mortality, largely related to mediated factors such as GGT, Vitamin D, and CRP. These findings suggest that lower serum AlkP level may reduce all-cause and cardiovascular mortality in general population.